The Influence Of Financial Technology (Fintech) On Student Financial Management (A Case Study Of Students At Politeknik Muhammadiyah Makassar) - Amelia, Ingrid; Jaya, Asri; Syahriani, A. Tenri (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the impact of Financial Technology (Fintech) on student financial management at Muhammadiyah Polytechnic Makassar. A quantitative approach was used with 92 respondents who are fintech users, using surveys and SPSS for data analysis. The results show a positive and significant influence (t = 5.201, p < 0.05), indicating fintech improves planning, controlling, and optimizing student expenses. These findings highlight fintech’s role in supporting better financial habits, but also underline the need for increased financial literacy to prevent excessive spending. This research suggests the importance of responsible fintech use to help students manage finances effectively and sustainably.